Neuroimaging predictors of response to cognitive remediation and social skills training: A pilot study in veterans with schizophrenia. (30th November 2019) - McClure, Margaret M.; Graff, Fiona S.; Triebwasser, Joseph; Perez-Rodriguez, M. Mercedes; Rosell, Daniel R.; Szeszko, Philip R.; Chu, King-Wai; New, Antonia S.; Siever, Larry J.; Hazlett, Erin A.
Highlights: Veterans with schizophrenia were highly engaged in this CRT + SST trial, with excellent attendance across cohorts. Following CRT + SST, participants demonstrated significant improvement in reasoning and problem solving, verbal learning, and social cognition. Baseline FA in the SLF predicted improvements in visual-spatial working memory while overall baseline FA predicted improvements in social cognition. Results support the concept that determining the neurobiology underlying individual differences in treatment response is important for precision medicine in psychiatry. Abstract: Neuroimaging may predict response to cognitive remediation therapy and social skills training (CRT + SST) in schizophrenia. Identifying biological predictors of response is crucial for treatment decision making given not all patients respond to such interventions. Nineteen veterans with schizophrenia enrolled in an 8-week trial of CRT + SST. Ten participants completed diffusion tensor imaging (DTI) at baseline. Baseline fractional anisotropy (FA) in the superior longitudinal fasciculus (SLF) and overall average FA predicted improvements in visual-spatial working memory, and social cognition, respectively. Neuroimaging may be useful in identifying therapeutic targets in schizophrenia.